CARBON DIOXIDE (CO) SEQUESTRATION IN MANGROVE LEAVES AT TANJUNG REJO VILLAGE - Dawolo, Alfandi Putra Jaya; Sudibyo, Mufti; Daulae, Abdul Hakim (Riwayat: Educational Journal of History and Humanities, 2025)
The Paluh Getah Mangrove Beach in Tanjung Rejo Village is a highly potential mangrove ecotourism site for carbon sequestration. This study aimed to assess the biomass content, carbon sequestration level, and comparative CO absorption in four mangrove leaf species (Avicennia marina, Excoecaria agallocha, Bruguiera gymnorhiza, and Ceriops tagal), as well as to analyze the effect of leaf thickness, width, and length on carbon uptake levels in Tanjung Rejo Village. Sampling was conducted at three stations determined using purposive sampling, each with three replications. Mangrove leaves were analyzed in the laboratory using the Walkley and Black method to determine carbon content. The results showed that Avicennia marina had the highest sequestration potential, followed by Bruguiera gymnorhiza, Ceriops tagal, and Excoecaria agallocha. Leaf length, width, and thickness measurements among the four species indicated variation in their CO absorption capacity.